Organizational learning and knowledge management: application within the Kwazulu- Natal department of public works - Khumalo, Sbongumusa Zimisele (Department of Construction Economics and Management, 2022)
Organizations invest millions in planning for investments and projects and apportion very little to nothing for evaluating and learning from them. This study reviewed the current knowledge management practices, particularly project closeout information at the KwaZulu-Natal Department of Public Works. This report provides a review and interpretation of knowledge management literatures in the project environment with a focus on the project closeout stage and the role and value that lessons learnt from post project reviews could potentially provide to project teams to improve current and future project implementation efficiency. A qualitative research approach, using thematic analysis and interpretive philosophy was used to analyse the data collected in this study. Semi-structured interviews, along with a survey questionnaire, were conducted with a selected sample of construction project managers and portfolio managers. Furthermore, the results of this study indicate that project managers see the value in cross project learning and senior management must have a structured knowledge management system in place that supports sharing of information and cross project learning that if implemented efficiently can aid in improving the performance and outputs for current and future projects. The proposed study will contribute to the fields of project management, cross project learning and knowledge management in the project environment. The study will look at means of fostering and improving the existing learning platforms within organizations with the aim of growing the organization's capacity and project implementation efficiency.